Application of nanobubbles in floating kinetics models for efficient oil removal from produced water - Daud, M F C; Khamidun, M H; Mohamed, R M S R; Ali, U F M; Razi, M A M (2023)
The primary objective of this study was to gain insight into the kinetics mechanism involved in the removal of oil from produced water using nanobubbles. A small-scale device called Solari - N MBG 0.35, manufactured by Solari Energy Limited, was employed to generate nanobubbles. Batch experiments were conducted to evaluate the impact of varying nanobubble concentrations on oil removal. The results revealed that at initial of contact time led to enhanced oil removal. This improvement was attributed to factors such as increased interfacial energy, improved mixing, and enhanced contact between the nanobubbles and oil droplets. However, after a 30-minute duration, the efficiency of oil removal reached a plateau due to the presence of smaller and more stable residual oil droplets. To analyze the nanobubble flotation process, the study employed five distinct models using experimental data. These models included the firstorder model, first-order model with a rectangular distribution, fully mixed factor model, improved gas/solid adsorption model, and second-order model. Statistical analyses were performed, considering parameters such as coefficient of determination (R2 ), root mean squared error (RMSE), mean absolute percentage error (MAPE), and mean absolute deviation (MAD). The fully mixed factor model, improved gas/solid adsorption model, and second-order model demonstrated excellent fitting performance at different contact times. These findings deepen our understanding of the oil removal efficiency of nanobubbles, emphasizing the significance of factors like concentration, contact time, and the selection of appropriate kinetic models. The study provides valuable insights into the application of nanobubbles in flotation processes and underscores the importance of selecting suitable models based on specific conditions and particle sizes